Poesia e santidade : alguns contributos para uma percepção do conceito de santidade, a partir de duas biografias devotas de religiosas do séc. XVIII português - Morujão, Isabel (1996)
Starting From the analysis of the devote biographies of two 18 th century nuns which include their production, the author explains such unusual binding of the poetic work in the biographic genre and shows how two narratives propose a clear articulation between poetry and holiness. It is suggeste that the selective perception of the saintly signs at such times was also operated from the perspective of a particular poetic topic.